Sectoral electricity demand and direct rebound effect in New Zealand - Rabindra Nepal; Muhammad Indra Al Irsyad; Tooraj Jamasb (Copenhagen Business School (CBS), Department of Economics, 2020)
This paper is one of the limited studies to investigate rebound effects in sectoral electricity consumption and the specific case of New Zealand. New Zealand, like other OECD economies, has aimed for energy efficiency improvements and reduced electricity consumption from 9.2 MWh per capita in 2010 to 8.6 MWh per capita in 2015. However, following a significant decline since 2010, electricity consumption in the main New Zealand sectors is increasing. Energy conservation could play an important role in meeting the growing demand for electricity but rebound effect can affect the effectiveness of conservation policies. We decompose the sectoral electricity prices to capture the asymmetric demand response to electricity price changes and estimate electricity demand elasticity during 1980 and 2015 to estimate the sectoral rebound effects. We find partial rebound effects of 54% and 23% in the industrial and commercial sector respectively while we find no partial rebound effect at aggregate sectoral level. The rebound effect is insignificant in the residential sector. These findings lead to policy recommendations for more sector specific energy conservation measures and policies.
hdl:10398/9814
Keywords: C32; Q41; Q48; L94; 330; electricity; demand; rebound; heating; time series analysis